Baltic herring (Clupea harengus membras) protein isolate produced using the pH-shift process and its application in food models. (August 2022) - Kakko, Tanja; Aitta, Ella; Laaksonen, Oskar; Tolvanen, Pasi; Jokela, Lauri; Salmi, Tapio; Damerau, Annelie; Yang, Baoru
Graphical abstract: Highlights: Protein isolate was extracted from Baltic herring through the pH shift process. Fishy odour was lower in the protein isolate compared to the raw material. Five odour compounds were less intense in the protein isolate compared to fish. Gel with protein isolate was similar to commercial surimis in terms of hardness. Baltic herring protein isolate could be applied in fish balls and surimi gels. Abstract: In this study, protein isolate was prepared from Baltic herring ( Clupea harengus membras ) using alkaline pH-shift process. The aim of this research was to characterize the protein isolate and to study its potential in food models. A special focus was placed on characterization of odour profile and volatile compounds contributing to the odour profile of the protein isolate using gas chromatography - olfactometry. 2, 3-Pentanedione, hexanal, 4( Z )-heptenal, 2, 4( E, E )-nonadienal, and three compounds tentatively identified as 1, 5( E )-octadien-3-ol, 1, 5( Z )-octadien-3-ol, and 1, 5( Z )-octadien-3-one were the most important odour-contributing compounds in the protein isolate (Nasal Impact Factor 83–100%, intensity 2.6–3.3 on a scale 0–4). 2-Methylpropanal, 2- and 3-methylbutanal, and three unknown compounds were less intense in the protein isolate than in the raw material, which might have contributed to the lower intensity of fishiness observed for the protein isolate (2.2 vs 3.3 on a scale 0–4). Surimi-type gels prepared from the Baltic herring protein isolate had texture properties (hardness and cohesiveness) similar to those of commercial products. Due to the abundancy of dark muscle tissue in Baltic herring, the protein isolate had a significantly lower whiteness (W = 63) compared to the commercial surimi products (W = 80–83). Increasing the solubilisation or precipitation pH did not improve the whiteness, but resulted in significantly softer, less cohesive, and less chewy gels. The findings of this study indicate that alkaline-based pH-shift processing is a potential way to increase the food application of Baltic herring.